The Relationship Between Academic Procrastination and Academic Stress Among Students - Azimah, Nurul; Nirwana, Herman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe: (1) students' academic procrastination, (2) students' academic stress, and (3) examine the relationship between academic procrastination and academic stress among students. This research uses a quantitative method with correlational analysis. The population of this study consists of 1,078 students enrolled in grades X, XI, and XII at SMAN 2 Bukittinggi for the July-December semester of the 2025/2026 academic year. The sample consists of 313 students selected through Stratified Random Sampling. Data were collected using an academic procrastination checklist and an academic stress checklist in the form of a Likert scale. The data were analyzed using descriptive analysis and Pearson Product Moment correlational analysis. The results show that (1) academic procrastination is in the low category, (2) academic stress is in the low category, and (3) there is a significant positive relationship between academic procrastination and academic stress among students. This study indicates that when the level of academic procrastination is low, academic stress is also low.